2021
DOI: 10.3390/microorganisms9061189
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Intestinal Protists of Zoonotic Relevance Detected in Pigs by Metabarcoding and Real-Time PCR

Abstract: Several parasite species are shared between humans and pigs. We explored the application of next-generation sequencing-based metabarcoding supplemented with real-time PCR to fecal DNAs from 259 samples from 116 pigs in Denmark to detect and differentiate single-celled intestinal parasites of zoonotic relevance. Enterocytozoon bieneusi, Balantioides coli, and Giardia duodenalis were observed in 34/37 (92%), 148/259 (57%), and 86/259 (33%) samples, respectively. Entamoeba polecki ST1, E. polecki ST3, and Entamoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Due to their high sensitivity and specificity, molecular methods such as conventional PCR (cPCR) or real-time PCR (qPCR) are often used [ 14 , 22 , 25 ]. In addition, next-generation sequencing (NGS) is gaining prominence in detection of Blastocystis and its subtypes [ 4 , 17 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high sensitivity and specificity, molecular methods such as conventional PCR (cPCR) or real-time PCR (qPCR) are often used [ 14 , 22 , 25 ]. In addition, next-generation sequencing (NGS) is gaining prominence in detection of Blastocystis and its subtypes [ 4 , 17 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…RL7 (Jacob et al 2016). Entamoeba hartmanni is also an endobiont of both humans and non-human primates, and this species has been identified recently in pigs via metabarcoding of faecal samples (Stensvold et al 2021b). Mature cysts contain four nuclei, but, with a maximum size of 10 µm, cysts of E. hartmanni are typically distinctly smaller than those of other species that produce quadrinucleated cysts, such as Entamoeba histolytica and Entamoeba dispar.…”
mentioning
confidence: 99%
“…A strongly limited ability to detect flagellate protozoa by both metagenomics and metabarcoding were observed in previous studies, especially with regard to G. duodenalis , but also for Cryptosporidium ( Parfrey et al, 2014 ; Ramayo-Caldas et al, 2020 ; Stensvold et al, 2021 ; Wylezich et al, 2019 ); the reason for this remains obscure. The authors suggested that the primers were not suitable for detection G. duodenalis and that the DNA extraction method was not appropriate for detection of Cryptosporidum ( Parfrey et al, 2014 ; Ramayo-Caldas et al, 2020 ; Stensvold et al, 2021 ; Wylezich et al, 2019 ). Nevertheless, the metaborcoding method used in the present study has been shown previously to enable detection of Cryptosporidium ( Stensvold et al, 2021 ), although with a somewhat reduced sensitivity.…”
Section: Discussionmentioning
confidence: 83%
“…The authors suggested that the primers were not suitable for detection G. duodenalis and that the DNA extraction method was not appropriate for detection of Cryptosporidum ( Parfrey et al, 2014 ; Ramayo-Caldas et al, 2020 ; Stensvold et al, 2021 ; Wylezich et al, 2019 ). Nevertheless, the metaborcoding method used in the present study has been shown previously to enable detection of Cryptosporidium ( Stensvold et al, 2021 ), although with a somewhat reduced sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation